Homocysteine and Oxidized Low Density Lipoprotein Enhance Platelet Adhesion to Endothelial Cells under Flow Conditions: Distinct Mechanisms of Thrombogenic Modulation - Dardik, R.; Varon, D.; Tamarin, I.; Zivelin, A.; Salomon, O.; Shenkman, B.; Savion, N. (Thrombosis and Haemostasis, 2000)
We investigated the effects of two well established risk factors for cardiovascular disease, homocysteine and oxidized low density lipoprotein (ox-LDL), on endothelial cell thrombogenicity. For this purpose we studied platelet adhesion to human endothelial cells (EC) under flow conditions at a shear rate of 350 s−1 following EC treatment with either homocysteine or ox-LDL. Treatment of EC with either homocysteine (1 or 10 mmol/L for 16 h) or ox-LDL (100 µg/ml for 16 h) resulted in a 2-3 fold enhancement in platelet adhesion. The enhancement in platelet adhesion induced by 1 mmol/L homocysteine, but not that induced by 10 mmol/L homocysteine, was absolutely dependent on fibrin formation. Homocysteine treatment has significantly increased the cell surface tissue factor (TF) activity and slightly reduced the expression of the intercellular adhesion molecule I (ICAM-1). In contrast, ox-LDL treatment upregulated ICAM-1 expression and had no significant effect on endothelial TF activity. Neither homocysteine nor Ox-LDL affected surface expression of the αvβ3 integrin. The homocysteine-induced enhancement in platelet adhesion was almost completely abolished by blockade of the EC TF activity by a polyclonal antibody. The enhancing effect of homocysteine was also greatly reduced by inhibition of the EC αvβ3 integrin, but was not affected by blockade of EC ICAM-1. On the other hand, ox-LDL-induced enhancement in platelet – EC adhesion was greatly inhibited by blocking ICAM-1 or αvβ3, but remained unaffected by inhibition of TF activity. Preincubation of platelets with the glycoprotein IIb-IIIa (GPIIb-IIIa) antagonist Reo-Pro has virtually abolished the enhancing effect of both homocysteine and ox-LDL. Our results suggest that homocysteine and ox-LDL might increase endothelial thrombogenicity by distinct mechanisms: homocysteine – by inducing TF activity, and ox-LDL – by upregulating ICAM-1, both of which enhance GPIIb-IIIa/fibrinogen dependent platelet adhesion to EC. The αvβ3 integrin, although not affected by EC stimulation, seems to play a crucial role in platelet-EC interaction regardless of the mechanism of EC perturbation.
Keywords: Homocysteine oxidized LDL; endothelial cells